Homework through a network: designing technologies to support learning activities within the home and between home and school - Fraser, Katie C. (2009)
Government policy and academic research both talk about transforming learning through networked technologies – sharing newly available information about the learning context with new partners to support lifelong learning activities, and giving learners increased power and autonomy. This thesis examines how such learning opportunities might be supported. In order to ground these learning opportunities in current educational activity it studies homework, which is an example of a learning activity that spans multiple contexts and the current roll-out point of networked technologies in UK schools.